Role of RTI in reforming the Indian administration - Kataria, S.K. (2009)
Right to information is an effective device to ignite and excell administrative reforms in a developing country where bureaucratic evils prevail at large. So as to achieve the goals of good governance and development administration, the administrative development and its overhauling are the prerequisite. Efficient and effective institutions are the key to rapid economic and social development and to translate promises into actionable programmes with the least possible cost. The RTI Act, 2005 is not only empowering the citizens but ensuring that administrative institutions and functionaries discharge their duties in the desired manner. It is RTI through which some basic administrative changes like record keeping, timeboundness, transparency, politeness and accountability are visible in the long-sicked Indian administration. - Reproduced.
Keywords: Public administration - India; Right to information